Ultrasound-guided perineural injection with platelet-rich plasma improved the neurophysiological parameters of carpal tunnel syndrome: A case report. (October 2017) - Kuo, Ying-Chen; Lee, Chia-Cheng; Hsieh, Lin-Fen
Highlights: If patients are refractory to conservative treatments, PRP may be an alternative. PRP injection may improve the neurophysiological parameters of CTS. Ultrasonography-guided injection frees entrapped structures more accurately. Abstract: Carpal tunnel syndrome (CTS) is a common and sometimes challenging condition, which causes pain; paresthesia; tingling of the thumb, index and long fingers; and even thenar weakness in the hands. The effectiveness of corticosteroid injections seems to be transient, and there is a lack of information around long-term effects in previous studies. In recent years, platelet-rich plasma (PRP) has proven to bean alternative as it encourages tissue regeneration. We hereby describe a patient with CTS showing significant improvements in electrophysiological parameters after receiving PRP injections. The results revealed significant improvements in the distal motor and sensory latencies as well as the sensory nerve action potential and compound muscle action potential amplitudes of the both median nerves. In summary, if patients are refractory to conservative treatments—such as splinting, oral medication, and corticosteroid injection—PRP may be used as an alternative before surgical intervention.